2016
DOI: 10.14486/intjscs517
|View full text |Cite
|
Sign up to set email alerts
|

Motivators, Constraints and Benefits of Participation in Sport As Perceived by the Students

Abstract: The purpose of this study was to evaluate the different motivators, constraints and general benefits of involvement in sports as perceived by the students. For this purpose, in addition to examining the existing literature for determining the principal motivators and constraints reported by the sport persons, viewpoint of the players was obtained and analyzed. Data from male and female student (N=370), 215 male and 155 female were obtained through a properly developed Likert type scale. The scale, offering 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(18 reference statements)
1
1
0
Order By: Relevance
“…Under the interpersonal constraint, lack of encouragement from friends and family to enable student-athletes to participate more significantly influenced sports participation among university student-athletes which is similar to the findings of a study by Marwat et al (2016). Results also indicated that Tennis/Badminton players were the most constrained, whereas basketballers were the least constrained, as also reported by (Stanek et al, 2015).…”
Section: Type Of Sport and Sports Participation Constraintssupporting
confidence: 85%
“…Under the interpersonal constraint, lack of encouragement from friends and family to enable student-athletes to participate more significantly influenced sports participation among university student-athletes which is similar to the findings of a study by Marwat et al (2016). Results also indicated that Tennis/Badminton players were the most constrained, whereas basketballers were the least constrained, as also reported by (Stanek et al, 2015).…”
Section: Type Of Sport and Sports Participation Constraintssupporting
confidence: 85%
“…Girls being together with boys for activities like dancing and swimming [34], being physically active during Ramadan [29], and wearing the physical education kit [35] were considered as some of the barriers for girls' participation in the classes. Another study conducted in Pakistan on university students depicted that socio-cultural barriers are one of the main constraints of sport participation which would be more evident among female participants [36].…”
Section: Female Participation In Sport In the Turkish And Muslim Contextmentioning
confidence: 99%